PENGEMBANGAN KEMAMPUAN GURU DALAM MELAKUKAN PENILAIAN PORTOFOLIO SISWA SEKOLAH DASAR - Fazilla, Sarah; Marisa, Riandi (Universitas Pendidikan Indonesia, 2015)
The purpose of this service is in order to share knowledge and experience in the form of seminars and workshops for school partners with regard to implementation of the alternatives assessment process which was implemented in primary schools. So that by applying an assessment that is expected to accommodate the function, purpose and principles of assessment and also provide additional information for teachers in designing an ideal alternative assessment. The asessmen which will be applied in this devotion is the assessment of the portfolio. This devotion is expected to have a high value of benefits both for proposing his own team, educators, students and the lesson itself. The targets of this devotion, namely; with the dedication is expected to be the subject of study and information for teachers as educators in formulating activities to increase the competence of teachers in elementary schools, which can be done through training, assessment and publishing technical reference and references associated with the knowledge, skills, and attitudes of teachers in carry out evaluation of learning by using portfolios, and can provide information reports on the results of this dedication to the principals in an effort to evaluate and improve the quality of the portfolio assessment program in the future.